The reality of brainstorming among students of the Academic Complex of Al-Mahalla Colleges at King Khalid University and the importance of strategic planning in its development - Mohamed, Reda Abdelfattah Ibrahim; Ibrahim, Ehsan Ibrahim AllahGabu (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the reality of brainstorming in the educational sector and to demonstrate the role of strategic planning in developing the skill of brainstorming among female students of the Academic Complex of Al-Mahalla Colleges at King Khalid University. The two researchers used the descriptive, correlational survey method. The study sample consisted of (85) individuals with a confidence factor of 95%. The tool consisted of a questionnaire consisting of (21) statements. It was distributed to a random sample of (86) female students in Al-Mahalla Colleges. The results of the study revealed that the overall tool obtained an average of (4.05 out of 5), i.e. a (large) role. Also, good strategic planning increases the ability to easily generate ideas. And that the cognitive skills of students work on defining responsibilities, which leads to the development of their brainstorming skills at the university. The results of the study proved the existence of a statistically significant relationship between strategic planning and the development of brainstorming, which would lead to a higher level of achievement among university students, The study reached a set of conclusions, the most important of which is that there is a direct positive relationship. The greater the application of strategic planning, the more it leads to an increase in the degree of development of the storming skill among the members of the research sample. Based on the results, the two researchers recommended the need to pay attention to clarifying the university's vision for students in order to quickly respond to learning. And the goals of the university must be flexible and able to adapt to unexpected changes.” Given the novelty of the subject of the study, the two researchers suggested the need to add complementary studies to the subject of the research.
Keywords: strategic planning; brainstorming; higher education sector; university students